2014
DOI: 10.2478/msr-2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Spectral EEG Features of a Short Psycho-physiological Relaxation

Abstract: Short-lasting psycho-physiological relaxation was investigated through an analysis of its bipolar electroencephalographic (EEG) characteristics. In 8 subjects, 6-channel EEG data of 3-minute duration were recorded during 88 relaxation sessions. Time course of spectral EEG features was examined. Alpha powers were decreasing during resting conditions of 3-minute sessions in lying position with eyes closed. This was followed by a decrease of total power in centro-parietal cortex regions and an increase of beta po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
116
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 10 publications
0
116
1
9
Order By: Relevance
“…Nevertheless, other results (e.g. a reduction in delta power and an increase of EEG complexity) contradict our findings [42,43]. Our study revealed that Snoezelen ® intervention modifies EEG activity, leading to a slowing of the EEG activity and a reduction of irregularity/complexity values.…”
Section: Discussioncontrasting
confidence: 54%
“…Nevertheless, other results (e.g. a reduction in delta power and an increase of EEG complexity) contradict our findings [42,43]. Our study revealed that Snoezelen ® intervention modifies EEG activity, leading to a slowing of the EEG activity and a reduction of irregularity/complexity values.…”
Section: Discussioncontrasting
confidence: 54%
“…The distances between nasion and anion is measured and the distance between the two ears is measured, and electrodes are placed at 10% and 20% distance as shown in fig.1, hence the name 10-20system [5].Electrode placements are labelled according to brain areas: F -frontal, C -central, T -temporal, P -posterior, and O -occipital. The electrical characteristic of EEG is its amplitude range in µV and frequency band in 0.5Hz to 60Hz [1] …”
Section: Introductionmentioning
confidence: 99%
“…In 1958, International Federation in Electroencephalography and Clinical Neurophysiology adopted calibration for electrode location called 10-20 electrode placement system [5] [14]. This system standardized the physical placement of electrodes and the labels of electrodes on the scalp.…”
Section: Introductionmentioning
confidence: 99%
“…The data acquisition of the human mind waves (EEGs) are collected from the electrodes [1] situated directly on the grey matter or upon the scalp which are called as Invasive and Non-invasive methods and that electrical activity between neurons known as voltage magnitude is plotted versus time. The electrical activity of the EEG signal is nothing but the amplitude of EEG signal.…”
Section: Introductionmentioning
confidence: 99%